Prevention of violence against women in household by the Indonesian laws - Arief, Hanafi (Opción, 2019)
This study will analyze in depth the prevention of violence inhousehold undertaken by the Indonesian government through the laws.This is a normative legal research with descriptive analysis. Theresults of the research show that in the prevention of domesticviolence, Indonesian government has used a specific law andregulation such as Domestic Violence Law 23 of 2004 based on theDeclaration of UNO on the Elimination of Discrimination againstWomen. In conclusion, to prevent violence in household, Indonesiaalso has used other related laws such as: Marriage Law 1 of 1974, andHuman Rights Law 39 of 1999.